Capacity development and Indigenous social enterprise: The case of the Rirratjingu clan in northeast Arnhem Land. (1st February 2018) - Spencer, Rochelle; Brueckner, Martin; Wise, Gareth; Marika, Bundak
Abstract: With the widespread shift from models of welfare to business-led development, capacity development offers a useful lens from which to consider the emergence of Indigenous social enterprise as a business-led development approach. We explore capacity development from the international development literature and identify capacity development principles in the context of an Indigenous social enterprise in remote northeast Arnhem Land. Here, Aboriginal Australians continue to experience poverty and marginalisation. This paper provides an ethnographic example of the relationship between Indigenous social enterprise and capacity development. Identifying principles of capacity development in this rich context reveals the remit of the Indigenous social enterprise privileges environmental stewardship and cultural maintenance.